The Relevance of Modern Genetic Concepts to the Al-Qur'an: DNA Analysis and Human Creation According to the Ministry of Religion's Scientific Interpretation - Suryana, Dede; Ghianovan, Jaka; Muzakki, Asgar (TAFSE: Journal of Qur'anic Studies, 2024)
The intersection of modern genetics and Islamic theology is a burgeoning field of inquiry. This study delves into how technological advancements, especially in genetics, complement the teachings of the Al-Qur’an. Modern genetics, which traces its origins to Gregor Mendel's pioneering work on heredity, provides a scientific framework for understanding the transmission of genetic information across generations. Contrary to the view that science and religion are mutually exclusive, this research, supported by the Ministry of Religion through the scientific interpretation found in Tafsir Ilmi Kemenag, demonstrates their potential synergy. It particularly focuses on Quranic verses that align with genetic principles, such as the developmental stages of a human embryo detailed in Surahs Ar-Rahman, Al-Insan, As-Sajadah, Al-Mu'min, and Al-Hajj. These verses metaphorically describe the embryonic stages that echo modern genetic descriptions of DNA's role in human development. Our findings illustrate that the Quran anticipates certain modern scientific discoveries, offering a unique blend of scriptural interpretation and empirical science to bridge the gap between faith and rational inquiry.